Chimeric plant calcium/calmodulin-dependent protein kinase gene with a neural visinin-like calcium-binding domain. - Patil, S (1995)
Calcium, a universal second messenger, regulates diverse cellular processes in eukaryotes. Ca2+ and Ca2+/calmodulin-regulated protein phosphorylation play a pivotal role in amplifying and diversifying the action of Ca(2+)-binding domain was cloned and characterized from lily. The cDNA clone contains an open reading frame coding for a protein of 520 amino acids. The predicted structure of CCaMK contains a catalytic domain followed by two regulatory domains, a calmodulin-binding domain and a visinin-like Ca(2+)-binding domain. The amino-terminal region of CCaMK contains all 11 conserved subdomains characteristic of serine/threonine protein kinases. The calmodulin-binding region of CCaMK has high homology (79%) to alpha subunit of mammalian Ca2+/calmodulin-dependent protein kinase. The calmodulin-binding region is fused to a neural visinin-like domain that contains three Ca(2+)-binding EF-hand motifs and a biotin-binding site. The Escherichia coli-expressed protein (approximately 56 kDa) binds calmodulin in a Ca(2+)-dependent manner. Furthermore, 45Ca-binding assays revealed that CCaMK directly binds Ca2+. The CCaMK gene is preferentially expressed in developing anthers. Southern blot analysis revealed that CCaMK is encoded by a single gene. The structural features of the gene suggest that it has multiple regulatory controls and could play a unique role in Ca2+ signaling in plants.